2018
DOI: 10.1016/j.funbio.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of phenotypic traits in the progeny of a Ceratocystis interspecific cross

Abstract: Ceratocystis fimbriata is a fungal plant pathogen that causes black rot on Ipomoea batatas. Based on inoculation studies on numerous tree species, the pathogen is known to be host specific. The closely related species, Ceratocystis manginecans, causes severe wilt on a broad range of tree hosts, including Mangifera indica, Acacia mangium and other leguminous tree species. The genetic factors underlying the pathogenicity and host specificity of Ceratocystis species have rarely been investigated. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Ceratocystis fimbriata causes black rot on Ipomoea batatas (sweet potato). Large disease outbreaks have recently re-emerged in the USA (Scruggs et al 2017) and infections have also been reported in China (Li et al 2016), Japan (Paul et al 2018) and other Asian countries (Fourie et al 2018;Paul et al 2018). In this study C. fimbriata refers to the I. batatas-specific species, recently epitypified by Marincowitz et al, 2020, and also referred to by some researchers as C. fimbriata f. sp.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Ceratocystis fimbriata causes black rot on Ipomoea batatas (sweet potato). Large disease outbreaks have recently re-emerged in the USA (Scruggs et al 2017) and infections have also been reported in China (Li et al 2016), Japan (Paul et al 2018) and other Asian countries (Fourie et al 2018;Paul et al 2018). In this study C. fimbriata refers to the I. batatas-specific species, recently epitypified by Marincowitz et al, 2020, and also referred to by some researchers as C. fimbriata f. sp.…”
Section: Introductionmentioning
confidence: 85%
“…Ceratocystis fimbriata and C. manginecans are closely related and can be induced to mate under laboratory conditions (Fourie et al 2018;Oliveira et al 2015). However, inoculations with each of these species onto I. batatas and different tree species have shown that C. fimbriata is highly specific to I. batatas while C. manginecans can infect several tree species but is not pathogenic to I. batatas (Baker et al 2003;Fourie et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, two to four genes may be responsible for the pathogenicity of the two sibling species Ceratocystis manginecan and Ceratocystis fimbriata on Acacia mangum and Ipomoea batatas (Fourie et al 2018;Fourie et al 2019). Similarly, one to two genes have been shown to be responsible for host specificity of Magnaporthe oryzae on foxtail millet in a cross between an isolate pathogenic on wheat and an isolate pathogenic on foxtail millet (Murakami et al 2003), and three genes have been shown to be responsible for host specificity of M. oryzae on wheat in a cross between an isolate pathogenic on rice and an isolate pathogenic on wheat (Tosa et al 2006).…”
Section: Valérie Caffier Phytopathologymentioning
confidence: 99%
“…The type species, Ceratocystis fimbriata, was first described in the USA in 1890 as the causal agent of black rot of Ipomoea batatas (Halsted 1890). It shows strong host specificity and does not infect tree hosts, in contrast to many other species in this genus (Baker et al 2003;Fourie et al 2018). The pathogen is known in various parts of the USA as well as in Asian countries including Papua New Guinea, China, Japan, Hawaii and New Zealand (Halsted and Fairchild 1891;Lewthwaite et al 2011;Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%